IPTEK BAGI MASYARAKAT PEMANFAATAN TURBOJET DRIVE PRODUK 3D PRINTING UNTUK PERAHU NELAYAN SUNGAI DESA SEMPAN-BANGKA - Hasdiansah Hasdiansah; Pristiansyah Pristiansyah; Indra Feriadi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Province of Bangka Belitung Islands has a large number of natural resources, including mining products, marine products, agricultural products, plantation products, and river products. One of the river products is fish and giant prawns which have high economic value which can be found in Bangka district, one of the places or rivers in Sempan village, Pemali sub-district. The river fishermen in the Pemali village fish and shrimp traditionally. The problem that occurs in these partners is that the boat still uses oars, this of course greatly slows down the movement in the river so that the catch of fish and giant prawns is small. Survey results on river fishermen partners on Sempan village, Pemali Bangka sub-district obtained data on the demand for a boat propulsion engine with low fuel consumption or a small engine displacement. The purpose of science and technology for river fishing communities is to increase the productivity of the catch of giant fish and prawns and as a means to save themselves from predators (crocodiles) when fishing for fish and shrimp in the river. The specific target of this IbM activity is expected to establish a cooperative and mutually beneficial relationship between partners and proposers from educational institutions. Partners get the right technology in the form of Turbojet Drive, 3D Printing product with a fuel-efficient engine. Agreed to propose to replace the boat propulsion system which originally used wooden oars to be replaced with a special “Turbojet Drive 3D Printing Product” propulsion with a fuel-efficient 58 cc engine. By replacing the offered boat propulsion, it is hoped that the targets and objectives of this IbM can be achieved and the catch of fish and giant prawns will increase. Thus, it is hoped that the standard of living of river fishermen will increase by using the appropriate technology offered by the proposing team.